Africa’s Poverty and Its Neo-Pentecostal “Liberators”: An Ecotheological Assessment of Africa’s Prosperity Gospellers - Golo, Ben-Willie K. (Pneuma, 2013)
The preponderance of various forms of liberation-oriented gospels among Africa’s neo-Pentecostals, particularly prosperity “gospelling,” should not be surprising when one considers the contexts within which they emerge. However, their narrow focus on the accumulation of wealth and material things as that which liberates from poverty is rather bewildering. Drawing on data collected from neo-Pentecostals, this article examines the definition of prosperity and the theological basis for such teachings, probes the environmental sustainability of the narrow wealth-seeking attitudes of these prosperity gospellers, and examines the ecological adequacy of the theology of salvation upon which prosperity gospelling is founded. The article concludes that the option available to the prosperity gospellers is a quest for liberation from poverty that correlates with the Christian vision for both human welfare and the health of the natural world.
free
Keywords: Africa; natural world; neo-Pentecostals; neo-pentecostal “liberators”; prosperity gospellers; theology of salvation